COVID-19 and contamination: impact on exposures to alcohol-based hand sanitizers reported to Texas Poison Control Centers, 2020. (3rd October 2021) - Phillips, Todd; Schulte, Joann M.; Smith, Eric Anthony; Roth, Brett; Kleinschmidt, Kurt C.
Abstract: Background: The COVID-19 pandemic has increased use of alcohol-based hand sanitizers (ABHS), creating shortages leading to additional production by new, non-traditional manufacturers. In June 2020, the Food and Drug Administration (FDA) issued warnings about methanol or 1-propanol contaminated brands of hand sanitizer. Exposure to methanol, including dermally, can cause kidney damage, blindness and death. Exposure to 1-propanol can cause severe acidosis and death. Chronic exposure may be more likely due to increased hand sanitizer use in 2020. Methods: We used generic codes for ABHS to characterize exposures reported to the Texas Poison Control Network in 2019 and 2020. For 2020 cases, we also used case narratives to identify cases considered COVID-19 -related and cases where the caller reported exposure to unknown ABHS with safety concerns, specifically identified brands on the FDA warning list or before that warning was made in June 2020. Results: Reported exposures to ABHS increased 72.5% between 2019 and 2020. In 2020, 10% of the cases were COVID-19 -related. COVID-19 -related cases in 2020 were likely to be older, to have a lower portion of young children exposed and to report chronic use of hand sanitizer. Similar trends were reported among cases who reported possible exposures to potentially unsafe ABHS products, including products on the FDA list. Most exposures were not referred for medical attention, and no deaths were reported among the Texas cases. Discussion: Callers reporting exposures to ABHS related to use prompted by the novel severe acute respiratory syndrome coronavirus 2 (COVID-19) and specific exposure to unsafe products differ from the traditional callers in being older, reporting chronic use and in healthcare facility (HCF) referral. The 72.5% increase in 2020 calls compared to 2019 cases differ from typical exposures, which often involve young children. Changes in manufacturing processes by additional manufacturers have produced potential exposure to toxic alcohol-containing products and others in Texas.